Produção e caracterização do kefir saborizado com polpa de cagaita (Eugenia dysenterica) - More, Juan Carlos Roberto Saavedra (2019)
Kefir is considered a beverage with many health benefits and is possibly one of the oldest probiotic food products. The objective was to develop different formulations of kefir flavored with cajita pulp, Eugenia dysenterica, evaluating its physico-chemical, microbiological, rheological, colorimetric, shelf life and sensorial acceptance characteristics. Nine formulations with different concentrations of sugar and cajita pulp were prepared. The formulations were fermented with the eXact® KEFIR 12 and YoFlex® Harmony 1.0 starter cultures, totaling 14 bacteria. The physico-chemical analyzes carried out for the raw material and for the formulations were: pH, acidity, moisture content, ashes, proteins, lipids, carbohydrates and total energetic value. Microbiological analyzes carried out in the formulations were: Most Likely Number of Coliforms at 35 ° C, Most Likely Number of Coliforms at 45 ° C and Salmonella sp. In the formulations were carried out, weekly, acidity analysis and lactic acid bacteria count to determine the shelf life. The analysis of variance and the Tukey test were used for the statistical analysis of the data. Kefir presented physicochemical characteristics according to the standards established by the legislation. Kefir formulations showed shelf life of eight weeks under refrigeration at 5 ° C, keeping lactic acid bacteria counts above 107 CFU / g and acidity below 1g lactic acid / 100g. With the exception of two formulations that did not contain sugar in their composition, the other formulations of kefir were well accepted in the sensory analysis, with notes between "slightly liked" and "extremely liked" attributes for appearance, color, aroma, flavor, consistency and overall impression. The formulations that had the highest grades for the flavor and overall impression attributes were those containing 10% sugar and 0% or 10% cashew pulp, and also those that had the highest grades for the purchase intent, with notes that Sensory evaluation form corresponded to "I would probably buy". The results obtained in the present work indicate that kefir can be produced industrially using starter cultures and present a long shelf life and good acceptance by the Brazilian consumer, which confirms it as a promising dairy product.